An Integrated Neural and Algorithmic System for Optical Flow Computation - Criminisi, Antonio; A. M. Gioiello, G.; Molinelli, D.; Sorbello, F. (1996 Italian Workshop on Neural Nets, 1996)
Motion detection plays a central role in several visual environments: knowledge of object velocities and trajectories is fundamental in scene interpretation and segmentation. This task appears a simple problem, but detecting moving objects is very difficult, in fact this is a problem that cannot be considered completely solved today [1] [2] [3].